2007
DOI: 10.1002/jbm.a.31519
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐micron and nanoscale feature depth modulates alignment of stromal fibroblasts and corneal epithelial cells in serum‐rich and serum‐free media

Abstract: Topographic features are generally accepted as being capable of modulating cell alignment. Of particular interest is the potential that topographic feature geometry induces cell alignment indirectly through impacting adsorbed proteins from the cell culture medium on the surface of the substrate. However, it has also been reported that micron-scale feature depth significantly impacts the level of alignment of cellular populations on topography, despite being orders of magnitude larger than the average adsorbed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 38 publications
(80 reference statements)
7
95
0
Order By: Relevance
“…However, with the same "ridge" width, the deeper the groove, the more pronounced "contact guidance occurred". And the results were in accordance with other researches; i.e., when the "ridge" width is fixed, the groove depth was the predominant factor in determining the occurrence of "contact guidance" [12,14,15,23] . Apart from the factors such as depth and width, researchers further investigated the threshold scale that can cause "contact guidance".…”
Section: The Major Factors To Influence the Occurrence Of "Contact Gusupporting
confidence: 91%
“…However, with the same "ridge" width, the deeper the groove, the more pronounced "contact guidance occurred". And the results were in accordance with other researches; i.e., when the "ridge" width is fixed, the groove depth was the predominant factor in determining the occurrence of "contact guidance" [12,14,15,23] . Apart from the factors such as depth and width, researchers further investigated the threshold scale that can cause "contact guidance".…”
Section: The Major Factors To Influence the Occurrence Of "Contact Gusupporting
confidence: 91%
“…We have previously demonstrated that feature depth of topographic features is a significant parameter, where increased groove depth resulted in an increase in the number of cells elongating and aligning in the direction of the grooves. 32 It is important to note, however, that differences in feature depths ranging from 200 to 450 nm, as measured by AFM (absolute or not) in this study, would not have elicited significantly different cellular responses.…”
Section: Resultsmentioning
confidence: 60%
“…Increasing feature height, while keeping constant inter-feature length, causes the space between adjacent grooves to become impervious to the cell membrane and integrins and therefore a decrease in adhesion stability occurs [70,71]. Analogous results have been observed on substrates presenting arrays of nanometric pits.…”
Section: Topo-cue-mediated Crosstalkmentioning
confidence: 64%